Isle of the Saints : Monastic Settlement and Christian Community in Early Ireland - Bitel, Lisa M., 1958- (Cornell University Press, 2019)
Isle of the Saints recreates the harsh yet richly spiritual world of medieval Irish monks on the Christian frontier of barbarian Europe. Lisa Bitel draws on accounts of saints' lives written between 800 and 1200 to explain, from the monks' own perspective, the social networks that bound them to one another and to their secular neighbors.